Itens de origem antrópica na dieta de peixes pelágicos capturados em cardumes associados no atlântico oeste equatorial - Mesquita, Grazielly Campos de (2019)
The present study aims to evaluate the occurrence of anthropogenic items, such as organic particulate matter (chum) and synthetic materials in the diet of five species of pelagic fish caught in the equatorial West Atlantic Ocean. Between 2011 and 2017, 807 stomachs from Thunnus albacares, Thunnus obesus, Coryphaena hippurus, Katsuwonus pelamis and Elagatis bipinnulata were collected around a buoy of atmospheric and oceanographic data collection (00ºN and 035ºW). The stomachs were weighed, analyzed and food items identified at the lowest possible taxonomic level. To evaluate the relationship between the species and their food items, Correspondence Analysis (CA), PERMANOVA and IRI were performed. The Morisita-Horn index was also used to verify the presence of an overlap between the diets of the species. We found that E. bipinnulata’s stomachs presented the highest percentage of anthropogenic items. The main items of anthropogenic origin that occurred in the stomachs were nylon ropes, plastic fragments, baits and entrails from organisms not belonging to the natural diet of the species. The Morisita-Horn index showed that Thunnus obesus had the lowest overlap of its diet when compared to the other species. The total presence of chum in the stomach contents of the fish was equivalent to 4.68%, while the synthetic material was 1.26%. The species most affected by the presence of materials of anthropogenic origin were the ones that feed in the oceanic epipelagic zone, up to 100m deep, which are T. albacares, C. hippurus, E. bipinnulata and K. pelamis. The species of T. obesus, which feeds on common prey in the mesopelagic zone, between 200m and 600m deep, did not present any of these materials in their stomach contents. Thus, we consider that anthropogenic materials are becoming increasingly frequent in the diet of organisms studied in the Atlantic Ocean. Therefore, is emphasized the importance of mitigating and alternative measures for the reduction of these materials, aiming the health of the individuals, the balance of the trophic and productive chain in which these species are inserted.